2006
DOI: 10.1345/aph.1g693
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Furosemide Continuous Infusion Following Cardiac Surgery

Abstract: A continuous infusion of furosemide is an effective and safe method of diuresis in patients undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Appropriate maintenance of the patient’s volume status is an important part of the perioperative management of patients undergoing cardiac surgery [79,80,81]. Patients often become volume overload after surgery, due in part to the large amounts of fluids received intra-operatively for cardiopulmonary bypass and hypotensive episodes [80].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Appropriate maintenance of the patient’s volume status is an important part of the perioperative management of patients undergoing cardiac surgery [79,80,81]. Patients often become volume overload after surgery, due in part to the large amounts of fluids received intra-operatively for cardiopulmonary bypass and hypotensive episodes [80].…”
Section: Resultsmentioning
confidence: 99%
“…If the hypervolemia is not corrected, it can contribute to the development of postoperative hypoxia, tissue edema, and delayed postoperative recovery [80,81]. One of the mainstays for postoperative fluid overload is the administration of furosemide [79]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A continuous infusion has been found safer in the surgical setting. 10 In a randomized trial furosemide bolus versus continuous IV infusion, the IV infusion was found superior. 11 The utility of continuous infusion has been confirmed in studies with an elderly population 12 even with severe heart failure.…”
Section: Diuretic Therapymentioning
confidence: 98%
“…To combat this, several strategies have been developed, such as repeated administration (often better than a large single dose) or addition of a thiazide-type diuretic to inhibit distal sodium resorption (92)(93)(94)(95)(96)(97)(98). Furosemide infusion is superior to, and at least as safe as, repeated large-dose boluses (95,(99)(100)(101)(102)(103). A disadvantage of intravenous infusions is that many hospitals mandate that such infusions be given in intermediate or even intensive care settings.…”
Section: Practical Tipsmentioning
confidence: 99%